O aspecto lúdico presente nos projetos pedagógicos de cursos de licenciatura em Matemática no estado do Rio Grande do Sul - Kegler, Natália Alessandra (2016)
In 2009, through the Extension Project “Mathmagic in the Classroom”, it was possible to get into contact with several Mathematics teachers seeking for a way to teach in a more playful way in the classroom. After several years of dedication and experience in that project; in 2013, many questions have arisen: does the pre-service Mathematics teacher have any contact with the playful way of teaching during the undergraduate years? Is it present in the curricula of pre-service teachers? Thus arose the current dissertation which aims to analyze how the ludic aspect is presented in the pedagogical curricula of pre-service Mathematics teachers. To accomplish this goal, first we conceptualized the ludic aspect researching the literature. As a second step, using a exploratory, documental and qualitative analysis of the curricula of pre-service Mathematics teachers offered by Universities in the State of Rio Grande do Sul active as of December 1995 and approved by MEC. As such it sought to study and contribute to the discussions regarding the curricula of pre-service Mathematics teachers, since the research in the curricula`s content regarding play activities, so far, no evidence has already been found, will provide ideas for further reflection on the part the universities, which are already adapting their curricula to see that there are still some gaps that need to be worked out. We conclude that the games and play activities are present in the researched curricula and remains the certainty that an activity or task need not be a game to fit within the playful aspect, since the same instigate, motivate and thus provide moments of creativity and learning, any activity will become playful.